Moral panics as civilising and decivilising processes? A comparative discussion - Rohloff, Amanda (Política y Sociedad, 2013)
This paper draws from a variety of case study examples of ‘moral panic analyses’, in combination with figurational analyses of the same topics, to comparatively explore the variant forms ‘moral panics’ take and how they develop, thereby analysing the multiple forms civilising processes can take. Using ‘moral panic’ as an illustrative example, this paper will discuss how and to what extent civilising processes can give rise to decivilising trends (in the form of moral panics) yet, at the same time, these moral panics can also bring about integrative ‘civilising’ effects in the form of civilising offensives that reflect possible long-term civilising trends (in the form of accelerated campaigns; a civilising ‘spurt’). Throughout this comparative discussion, I aim to highlight not only the complexity of civilising processes, but also the complex civilising and decivilising aspects of moral panics, thereby overcoming the dichotomous normative conceptualization of moral panics as being either ‘good’ or ‘bad’ panics. The paper then moves onto a discussion of the paradoxical idea of viewing moral panics as civilising and decivilising processes. Drawing from Foucault, Elias, and moral panic, the paper concludes with a discussion of a rethinking of civilising and decivilising processes, intended and unintended developments, short-term and long-term processes, and the role of knowledge in civilising processes.
Keywords: alcohol; climate change; drugs; Michel Foucault; Norbert Elias; moral panic